Cardiorespiratory fitness in adolescents Aptidão cardiorrespiratória em adolescentes - Minatto G. (2017)
© 2016 Consejería de Turismo y Deporte de la Junta de AndalucíaObjective The aim of this study was to determine the prevalence of cardiorespiratory fitness and its association with sociodemographic characteristics and body composition in adolescents. Method This is a cross‐sectional study with 601 students (14‐17 years) of the public school system in the Mid‐western state of Santa Catarina. Cardiorespiratory fitness was measured by the 20‐meter back‐and‐forth test. Information on gender, age and economic status, body weight, height, waist circumference and skinfold thickness were collected. Statistical analysis (Mann‐Whitney U, chi‐square and logistic regression tests) was performed, with 5% significance level. Results The prevalence of inadequate cardiorespiratory fitness was 61.1%, being higher in boys and in those with inadequate body composition. Inadequate body composition was associated with poor cardiorespiratory fitness even after adjusted by sex, age and economic status. Conclusion It was concluded that most adolescents showed inadequate levels of cardiorespiratory fitness and the association between body composition and inadequate cardiorespiratory fitness is independent of sociodemographic characteristics of adolescents.